Pathways : Andreas Barban - Memorial University of Newfoundland. Educational Television Centre (Memorial University of Newfoundland. Educational Television Centre, 1983)
In this episode of Pathways, Cathy Boak interviews concert pianist Andreas Barban. "A Memorial University Television Production, ©1983"